ANALISIS HASIL VOLTAGE DETECTOR THE SKY DANCER 500W PADA PEMBANGKIT LISTRIK TENAGA BAYU SKALA MIKRO DI PT. LENTERA BUMI NUSANTARA - Dendy Reza Anfasha; M. Rinaldi Robiansyah; Dian Budi Santoso (Politeknik Harapan Bersama Tegal, 2022)
Voltage Detector is a tool that can read the output voltage value of a generator. Voltage detector on the controller serves as a voltage detector input controller derived from the generator. The output of the Voltage detector is an analog signal processed by the microcontroller to then activate the relay and then forward the input voltage when the input voltage is in accordance with the provisions to the rectifier circuit. The output of this Voltage detector is an analog signal so it needs to be connected with a microcontroller ADC for processing. Voltage detector is prepared using the concept of voltage divider between 2 pieces of resistance. At resistance 1, it is the result of a series and parallel circuit relationship between the 9 receipts used. When the maximum rectifier output voltage is 200V and the maximum output voltage of the designed detector is no more than 5V, then the value of the components used is set according to the needs. Resistor resistance values 1 to resistors 9 are determined at 56KΩ and capacitors are used as large as 1μF.